2020
DOI: 10.1111/acer.14517
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Executive Function Abilities in Recently Detoxified Patients with Alcohol Use Disorder: Evidence from a Cluster Analysis

Abstract: Background Impairments of executive functions (EF) have been consistently reported in patients with alcohol use disorder (AUD), mostly in studies which were based on comparisons of means between groups. However, given the high heterogeneity in AUD patients, this approach could actually cover a wide range of EF patterns. In the present study, we addressed the paucity of the literature about cognitive heterogeneity in AUD by applying a cluster analytical approach on EF measures. Methods Seventy‐eight withdrawn A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…Results indicated that EF and ToM specificities were present in approximately half of FH+ participants (53.33%), whereas the other FH+ participants had EF and ToM performances within the normal range (47.67%). This result echoes previous findings in AUD which have reported EF and ToM alterations in one out of two patients, suggesting heterogeneous cognitive patterns in this pathology (Maurage et al., 2015; Schmid et al., 2021). Prior studies of EF and SC abilities in FH+ individuals have yielded divergent results, with some suggesting EF and SC alterations (Dougherty et al., 2015; Henderson et al., 2018) and others equivalent behavioral performances across FH+ and FH− individuals (DeVito et al., 2013; Schmidt et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results indicated that EF and ToM specificities were present in approximately half of FH+ participants (53.33%), whereas the other FH+ participants had EF and ToM performances within the normal range (47.67%). This result echoes previous findings in AUD which have reported EF and ToM alterations in one out of two patients, suggesting heterogeneous cognitive patterns in this pathology (Maurage et al., 2015; Schmid et al., 2021). Prior studies of EF and SC abilities in FH+ individuals have yielded divergent results, with some suggesting EF and SC alterations (Dougherty et al., 2015; Henderson et al., 2018) and others equivalent behavioral performances across FH+ and FH− individuals (DeVito et al., 2013; Schmidt et al., 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Whereas some FH+ individuals may have EF and SC difficulties, others may have no such cognitive specificities (Long et al, 2017). The fact that, in a parallel way, several studies have highlighted heterogeneous EF (Schmid et al, 2021) and SC (Maurage et al, 2021) abilities among detoxified patients with AUD lends further weight to this hypothesis. Up to now, studies among FH+ individuals have relied on group comparisons to assess the presence of EF and SC specificities.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, executive dysfunction interferes with motivational processes to abandon excessive drinking patterns, may comprise an individual's effort towards sustained abstinence, and may increase the risk of relapse. As a result, it may generally impair the ability to benefit from treatment [16,17]. Despite accumulating evidence on the impact of alcohol-related executive disfunction, literature on treatment and treatment outcome is sparse and inconclusive [18].…”
Section: Of 12mentioning
confidence: 99%